Comparative Efficacy and Safety of Oral Tranexamic Acid, 1% Arbutin Cream, and Their Combination in the Treatment of Melasma in Sulaymaniyah City: A Randomized Controlled Trial - Rashid, Hanaa Jaafar Hama; Abdalla, Darsim Mohammed (Journal of Sulaimani Medical College, 2025)
Background: Melasma is a prevalent acquired pigmentary disorder, often affecting women with Fitzpatrick skin types III-VI. Despite various treatment modalities, achieving complete resolution remains challenging due to frequent recurrences. This study evaluates the efficacy and safety of oral tranexamic acid (TXA), topical 1% arbutin cream, and their combination, addressing gaps in long-term therapeutic strategies. Patients and Methods: This open-label RCT, conducted at the Shahid Jabar Dermatology Center in Sulaymaniyah (Dec 2024–Jun 2025), included 120 melasma patients. They were randomized into three groups: Group A (oral TXA), Group B (topical 1% arbutin), and Group C (both). Melasma severity was assessed at baseline, 1, 2, and 3 months. Patient satisfaction was measured with a 5-point Likert scale, and adverse effects were monitored. Follow-up lasted 3 months after treatment discontinuation. Results: Baseline mMASI scores were similar across groups. After 3 months, Group C showed the greatest reduction (4.25 ± 2.13), followed by Group A (5.70 ± 3.15) and Group B (5.96 ± 2.99). Group C had the highest patient satisfaction (42.5%) and the lowest recurrence rate (14%). Adverse effects were minimal: epigastric pain in Groups A (20%) and C (17.5%), and skin irritation in Group B (2.5%). Group C also demonstrated significantly better outcomes compared to Group B (P = 0.007). Conclusion: Combination therapy with oral TXA and topical arbutin showed greater efficacy, higher satisfaction, and lower recurrence rates than monotherapy, providing a more durable solution for melasma. Further research is needed to optimize long-term outcomes.
Keywords: Arbutin; Combination Therapy; Melasma; mMASI score; Tranexamic acid